2023
DOI: 10.1038/s41598-023-30462-w
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas alcaliphila NEWG-2 as biosorbent agent for methylene blue dye: optimization, equilibrium isotherms, and kinetic processes

Abstract: In comparison to physicochemical and chemical methods, microbial dye biosorption is regarded as an eco-effective and economically viable alternative and is a widely applied method due to its high efficiency and compatibility with the environment. Therefore, the idea of this study is to clarify to what extent the viable cells and the dry biomass of Pseudomonas alcaliphila NEWG-2 can improve the biosorption of methylene blue (MB) from a synthetic wastewater sample. The array of Taguchi paradigm has been conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…As a result, the population can be divided into two or more homogeneous groups. These homogeneous sets are built using the most substantial differentiator on the input variables [ 27 , 80 ]. No information is available about the combination of DT with equilibrium isotherms and kinetic studies for the determination of relative variable importance and modeling the biosorption process.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the population can be divided into two or more homogeneous groups. These homogeneous sets are built using the most substantial differentiator on the input variables [ 27 , 80 ]. No information is available about the combination of DT with equilibrium isotherms and kinetic studies for the determination of relative variable importance and modeling the biosorption process.…”
Section: Resultsmentioning
confidence: 99%
“…The high correlation coefficients (R 2 = 0.977) indicated that the Langmuir model explains the Congo red biosorption equilibrium by the de-oiled biomass in the tested concentration ranges. It was stated that the Langmuir isotherm depends on the hypothesis of monolayer coverage of the tested dye onto a biosorbent with the homogenous surface, i.e., the biosorbent consists of similar sites with equal binding energy [91].…”
Section: Biosorption Of Congo Red By De-oiled Yeast Biomassesmentioning
confidence: 99%